Self-assembly, interfacial properties, interactions with macromolecules and molecular modelling and simulation of microbial bio-based amphiphiles (biosurfactants). A tutorial review - Baccile, Niki; Seyrig, Chloé; Poirier, Alexandre; Alonso-de Castro, Silvia; Roelants, Sophie L. K. W; Abel, Stéphane (Green chemistry : an international journal and green chemistry resource : GC, 2021)
Chemical surfactants are omnipresent in consumer products, but they are the subject of environmental concerns. For this reason, the complete replacement of petrochemical surfactants by biosurfactants constitutes a holy grail, but this is far from possible in the near future. Although the "biosurfactants revolution" has not yet occurred, mainly due to the higher cost and lower availability of biosurfactants, another reason could explain this fact: poor knowledge of their properties in solution. This tutorial review aims to review the self-assembly properties and phase behavior, experimentally (sections 3.3 and 3.4) and through molecular modelling (section 6), in water of the most important microbial biosurfactants (sophorolipids, rhamnolipids, surfactin, cellobiose lipids, glucolipids) as well as their major derivatives. A critical discussion of such properties in light of the well-known packing parameter of surfactants is also provided (section 3.5). The relationship between the nanoscale self-assembly and macroscopic material's properties, including hydrogelling, solid foaming, templating or encapsulation, is specifically discussed (section 3.7). We also present their self-assembly and adsorption at flat and complex air/liquid ( e.g. , foams), air/solid (adhesion), liquid/solid (nanoparticles) and liquid/liquid ( e.g. , emulsions) interfaces (section 4). A critical discussion on the use of biosurfactants as capping agents for the development of stable nanoparticles is specifically provided (section 4.2.4). Finally, we discuss the major findings involving biosurfactants and macromolecules, including proteins, enzymes, polymers and polyelectrolytes. Amphiphiles obtained by microbial fermentation, known as biosurfactants or bioamphiphiles, are reviewed in terms of their solution experimental and theoretical self-assembly properties, interface properties and interactions with macromolecules.